Combination of serum CA19-9 and CA125 levels and contrast-enhanced ultrasound parametric data facilitates to differentiate ovarian serous carcinoma from ovarian malignant epithelial cancer. Issue 16 (April 2018) - Zhang, Wei; Wang, Liying; Xin, Zhongqiu
Abstract : Abstract: Ovarian serous carcinoma (OSC) is semimalignant ovarian tumors that localized in the ovary at the initial presentation, and can be surgically resected in an excellent prognosis. In contrast, surgical treatment plus adjuvant chemotherapy for ovarian malignant epithelial cancer (OMEC) is the standard treatment stratagem that is painful with poor prognosis and cost quite expensively. Thus, the accurate preoperative differentiation of OSC from OMEC is important for determining the treatment methods and decreasing the cost for individual patients. This study aims to determine whether contrast enhanced ultrasound (CEUS) together with CA19-9/CA125 can improve the ability to differentiate ovarian serous carcinoma from ovarian malignant epithelial cancer. The positive rate of cancer antigen (CA) 199 and CA125 in ovarian malignant epithelial tumors was 68% and 94%, respectively, which was a higher incidence than in the serous carcinoma. The mean serum CA19-9 and CA125 concentration was significantly higher in the patients with ovarian malignant epithelial tumors (CA19-9, 514.0 ± 104.8 U/mL; CA125, 440.0 ± 154.8 U/mL) than that in the patients with ovarian serous carcinoma (CA19-9, 58.0 ± 14.3 U/mL; CA125, 63.0 ± 25.8 U/mL). The time to peak in ovarian serous carcinoma was significantly longer than in ovarian malignant epithelial tumors. However, the peak intensity, area under the curve, and washout time in ovarian serous carcinoma were significantly lower than in ovarian malignant epithelial tumors. The addition of CA19-9/CA125 increased the sensitivities from 79% CEUS only to 85% for CEUS plus CA19-9/CA125 data, and increased the specificities from 65% CEUS only to 91% for CEUS plus the CA19-9/CA125 information. Thus, the addition of the serum CA19-9/CA125 levels to parametric CEUS data was of significant diagnostic value for differentiating OSC from OMEC.